ANALISIS KEBUTUHAN PENGEMBANGAN STORYBOOK INTERAKTIF BERBASIS MULTIMEDIA DALAM MENULIS TEKS DESKRIPSI PADA SISWA KELAS IV SEKOLAH DASAR - Ramadani, Dilla Aulia; Anggi Citra Apriliana; Arita Marini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the needs for developing a multimedia-based interactive storybook to support descriptive text writing among fourth-grade elementary school students. A descriptive method was used at SDN Jatimekar VII through classroom observation, teacher interviews, and needs questionnaires involving 31 fourth-grade students and 29 fifth-grade students whose questionnaires were valid for analysis. The data were analyzed descriptively using percentages. The results show that 77.4% of fourth-grade students did not fully know what to write when describing nearby objects, and 51.6% felt bored when learning only through textbooks and the classroom board. In addition, 79.3% of fifth-grade students still experienced difficulties in organizing sentences, describing object details, or developing a complete descriptive text. These findings indicate the need for a multimedia-based interactive storybook that provides visual, verbal, audio, and step-by-step scaffolding to help students write descriptive texts more systematically.